2001
DOI: 10.1111/j.1469-7793.2001.0851e.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the control of head movements in seated humans: a link with whiplash injuries?

Abstract: 1. The aim of this study was to determine how context and on-line sensory information are combined to control posture in seated subjects submitted to high-jerk, passive linear accelerations. Subjects were seated with eyes closed on a servo-controlled linear sled. They were asked to relax and received brief accelerations either sideways or in the fore-aft direction. The stimuli had an abrupt onset, comparable to the jerk experienced during a minor car collision.2. Rotation and translation of the head and body w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
73
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(91 citation statements)
references
References 53 publications
18
73
0
Order By: Relevance
“…A strict stiff strategy might cause muscle fatigue or myalgia while a relaxed strategy, depending on passive structures, might increase the risk for injury in joint structures and tissues. Contrary to Vibert et al (2001), who found no or little adaptation in sideways reactions, seated postural reactions in the forward direction have been found to adapt after the first perturbation with decreased EMG amplitude over time [18,19]. If seated postural reactions in sideways directions adapts or not is still an unanswered question.…”
Section: Adaptation Of Postural Reactions In Seated Positions and Infmentioning
confidence: 76%
See 4 more Smart Citations
“…A strict stiff strategy might cause muscle fatigue or myalgia while a relaxed strategy, depending on passive structures, might increase the risk for injury in joint structures and tissues. Contrary to Vibert et al (2001), who found no or little adaptation in sideways reactions, seated postural reactions in the forward direction have been found to adapt after the first perturbation with decreased EMG amplitude over time [18,19]. If seated postural reactions in sideways directions adapts or not is still an unanswered question.…”
Section: Adaptation Of Postural Reactions In Seated Positions and Infmentioning
confidence: 76%
“…An increased segment angle should be possible as the EMG amplitudes was reduced. However, deeper muscles might be more active [8,30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations